1991
DOI: 10.1080/02652039109373981
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of aflatoxins and aflatoxin‐producing moulds in fresh and processed meat in Egypt

Abstract: A survey was carried out to detect aflatoxins and isolate aflatoxigenic moulds contaminating fresh and processed meat products. The fungal contamination was examined in 215 samples of fresh and processed meat products and 130 samples of spices used in the meat industry collected from different local companies in Cairo, Egypt. Processed meat products such as beefburger, hot-dog, kubeba, sausage, luncheon meat had the highest count of moulds as compared with fresh and canned meat. Out of 150 samples of meat prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 11 publications
3
46
3
Order By: Relevance
“…Contamination of meat and meat products are common due to ubiquitous distribution of such microorganisms which lead to spoilage and/or food-borne mycotoxicosis [2,3]. The environment in slaughter houses, butcher shops and refrigerators are considered as the main source of fungal contamination of meat [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Contamination of meat and meat products are common due to ubiquitous distribution of such microorganisms which lead to spoilage and/or food-borne mycotoxicosis [2,3]. The environment in slaughter houses, butcher shops and refrigerators are considered as the main source of fungal contamination of meat [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial pathogen commonly regarded as having the highest tolerance to reduced a w or increased salt concentration is Staphylococcus aureus (13). Mycotoxigenic or antibiotic-producing mold species can grow on meat products (1,5,14,15,17) and at lower a w values than are tolerated by S. aureus. Thus, these molds are a possible food safety hazard for RTE meat products.…”
mentioning
confidence: 99%
“…It is therefore, suggested that withdrawal of animals from contaminated feeds onto mycotoxin free diets for 3-4 weeks could have allowed for sufficient withholding period to clear the muscles and organs from the toxins. Despite the low carryover rates of the toxins into animal tissues, AF contaminate fresh and processed meat (especially liver and kidney) at toxicologically significant levels of up to 325µg/kg in Egypt (Aziz and Youssef, 1991;Abdelhamid, 2008). It is only proper to indicate further herein that consumption of animal visceral organs (kayan chiki) may constitute a major source of AF exposure than muscle.…”
Section: Animal Tissuesmentioning
confidence: 99%
“…According to these authors, contamination of the toxins has been observed in ginger, garlic and capsicum. A survey conducted for aflatoxigenic fungi and AF in spices from Egypt (Aziz and Youssef, 1991) found black and white pepper contaminated with AF at unhealthy levels (range: 22-35 µg/kg). Zinedine et al (2006) found natural presence of AFB 1 in black pepper, ginger, red paprika and cumin from Morocco at average levels of 0.09, 0.63, 2.88 and 0.03µg/kg, respectively, with the highest level of contamination found in red paprika (9.68µg/kg).…”
Section: Other Foodsmentioning
confidence: 99%